2002
DOI: 10.1097/00001721-200206000-00007
|View full text |Cite
|
Sign up to set email alerts
|

High doses of atorvastatin do not affect activity of prothrombinase in patients with acute coronary syndromes

Abstract: Membrane-dependent coagulation processes play a key role in acute coronary syndromes (ACS), where the generation of thrombin depends on the complex of activated factors X and V (prothrombinase complex) assembled on activated platelets. The aim of the present study was to evaluate prothrombinase activity in patients with ACS and to examine the effect of treatment with 80 mg/day atorvastatin on prothrombinase activity. Blood samples were obtained at admission from 22 patients with ACS, and then again at 2 weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 30 publications
0
5
1
1
Order By: Relevance
“…In a study of Bolaman et al [5] atorvastatin did not significantly change levels of hemoglobin, nor the number of white blood cells and platelets. Other data indicated that prothrombinase activity in patients with acute coronary syndromes is not influenced by highdose atorvastatin (80 mg/d) [22]. However, high-dose atorvastatin had no effect on major hemorheologic variables in our current investigation.…”
Section: Discussioncontrasting
confidence: 65%
“…In a study of Bolaman et al [5] atorvastatin did not significantly change levels of hemoglobin, nor the number of white blood cells and platelets. Other data indicated that prothrombinase activity in patients with acute coronary syndromes is not influenced by highdose atorvastatin (80 mg/d) [22]. However, high-dose atorvastatin had no effect on major hemorheologic variables in our current investigation.…”
Section: Discussioncontrasting
confidence: 65%
“…24 On the other hand, statins, even in high doses, do not diminish prothrombinase activity, as serially measured by the plasma levels of prothrombin fragment 1±2 in patients with acute coronary syndromes. 25 Obviously, large randomized studies are needed to determine the clinical importance, validity, and meaningfulness of the proposed beneficial pleiotropic effects of statins. 26…”
Section: Study Resultsmentioning
confidence: 99%
“…Furthermore, CD40 ligation is associated with the induction of COX-2 in endothelial cells [12]. Statins, which besides lipidlowering properties also have anti-inflammatory and anti-thrombotic effects, have been shown to interfere with CD40/CD40L signaling at several levels [10,13,14].…”
Section: Introductionmentioning
confidence: 99%